Directors' perceptions of best practice in corporate governance in Australia - McCabe, Margaret (Curtin University, 2002)
In this study directors of public listed companies around Australia gave their perceptions of best practice in corporate governance. A qualitative methodology within the constructivist paradigm was used along with a questionnaire thus making it a linked study. Mechanisms to assist in demonstrating rigour in the research process were developed and implemented as part of the research. The findings presented a description of best practice in corporate governance and a definition of corporate governance. Emerging from the findings was a model of best practice that was consistent with complex adaptive systems theory. Stakeholder theory was seen to provide the mechanism for developing activities that support the best practice model.